2013
DOI: 10.2169/internalmedicine.52.1180
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Patients who Developed Hepatocellular Carcinoma after Hepatitis C Virus Eradication with Interferon Therapy: Current Status in Japan

Abstract: Objective We attempted to elucidate the clinical features of chronic hepatitis C patients who develop hepatocellular carcinoma (HCC) after achieving a sustained viral response (SVR) to interferon (IFN) therapy. Methods The clinical features of 130 patients at 19 hospitals who developed HCC after obtaining an SVR were retrospectively reviewed. Results Overall, 107 (82%) of the 130 patients were men, with 92 (71%) being ! 60 years of age and 76, 38 and 16 developing HCC within 5, 5-10 and 10-16.9 years after IFN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…Many studies [9,10,11,12] have reported on risks for HCC development in patients with SVR who received IFN-based treatment. However, there are few reports on the recurrence of definitively treated HCC in patients with SVR, and on their long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies [9,10,11,12] have reported on risks for HCC development in patients with SVR who received IFN-based treatment. However, there are few reports on the recurrence of definitively treated HCC in patients with SVR, and on their long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of publications suggesting that the rate of HCC may be as high as 5% in patients experiencing an SVR. [35][36][37] Those studies are, however, primarily in Asian and European populations and do not contain significant numbers of AA. The primary risk factors for developing HCC in patients with SVR are males with genotype 1 and cirrhosis at the time of viral clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Nationwide data reveal that 2.4% (109/4,542) of Japanese patients who achieved SVR developed liver cancer during an observation period of approximately 5.5 years [15]. The longest interval between SVR and cancer onset was more than 15 years.…”
Section: α-Fetoprotein (Afp)mentioning
confidence: 99%